Diazepam tolerance: effect of age, regular sedation, and alcohol. Issue 6441 (11th August 1984) - Cook, P J; Flanagan, R; James, I M
Abstract : The dose of intravenous diazepam required for sedation was estimated in a series of 78 patients aged 17-85 years given the drug for dental and endoscopic procedures. Multiple regression analysis showed a significant correlation (r = 0.71; p less than 0.001) between dose and age, body weight, the taking of regular sedation, and the taking of more than 40 g alcohol daily, but there were no differences in the doses required between men and women, smokers and non-smokers, inpatients and outpatients, or dental and endoscopy patients. Patients aged 80 required an average dose of 10 mg and patients aged 20 an average dose of 30 mg, and the dose required was much higher in those receiving regular sedation or having a high alcohol intake. Plasma total and free diazepam concentrations were measured in the second half of the series of patients (n = 37). Plasma concentrations required for sedation fell twofold to threefold between the ages of 20 and 80 and were significantly higher in those taking regular sedation or alcohol. Differences in the acute response to diazepam appeared to be due to differences in the sensitivity of the central nervous system (pharmacodynamic tolerance) rather than to differences in pharmacokinetic factors.